Determining dengue risk factors in Selangor, Malaysia using regression approach - Ghani, Nurul Akmar (2020)
Dengue has become a burden to the world as dengue infection now occurs in more countries compared to before 1990s. In Malaysia, Selangor records the highest number of dengue cases every year. This study is done to investigate the risk factors that cause dengue outbreaks in Selangor. Data on knowledge, attitude and practice (KAP) together with environmental conditions were collected in hotspot and non-hotspot dengue area using questionnaires in 2015 and 2016. Data on weather in Selangor was obtained from the Malaysian Meteorological Department, and data on population distribution was obtained from the Department of Statistics Malaysia to compare with data on dengue incidences obtained from Selangor State Health Department. KAP data on communities living in hotspot and non-hotspot areas were investigated, and differences in knowledge and attitude marks were significant at p-value of 0.003 and <0.001 by T-Test, respectively. Environmental cleanliness on both areas was also examined and result shows hotspot areas were dirtier, with p-value of <0.001. Data on weather, relative humidity, mean 24-hour temperature, rainfall amount and number of rainy days were analyzed, and various correlation levels were found between weather and dengue incidences in all districts. The effect of population density on dengue was observed. District with highest population density, Petaling recorded the highest dengue incidences in both years. Logistic regression on all risk factors was done to produce the final model, which concludes that environmental condition, human attitude, and population density are the most probable risk factors that cause dengue transmission. The qualitative observation was done to look at the condition of both areas, and it confirmed that people in non-hotspot areas display better attitude and cooperation towards taking care of their surroundings. This shows that hygienic inspection and health education on dengue should be focused on hotspot areas to reduce the risk of dengue transmission.